Integrals at secondary school - Anynis, Antanas; Šinkūnas, Juozas (Lietuvos matematikos rinkinys, 2023)
Teaching of integrals in Lithuania, Denmark and France is presented. It is suggested to progress to three levels teaching of mathematics.
Keywords: mathematics; programme; curriculum; integral; examination